Asymmetric Atlantic continental margins - Vangone A.; Doglioni C. (Geoscience Frontiers, 2021)
We analyze the gross crustal structure of the Atlantic Ocean passive continental margins from north to the south, comparing eleven sections of the conjugate margins. As a general result, the western margins show a sharper continental-ocean transition with respect to the eastern margins that rather show a wider stretched and thinner margin. The Moho is in average about 5.7°±1° dipping toward the interior of the continent on the western side, whereas it is about 2.7°±1° in the eastern margins. Moreover, the stretched continental crust is on average 244 km wide on the western side, whereas it is up to about 439 km on the eastern side of the Atlantic. This systematic asymmetry reflects the early stages of the diachronous Mesozoic to Cenozoic continental rifting, which is inferred as the result of a polarized westward motion of both western and eastern plates, being Greenland, Northern and Southern Americas plates moving westward faster with respect to Scandinavia, Europe and Africa, relative to the underlying mantle.